If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -8 + y = 46 + 3y + -4y Reorder the terms: -8 + 4y + y = 46 + 3y + -4y Combine like terms: 4y + y = 5y -8 + 5y = 46 + 3y + -4y Combine like terms: 3y + -4y = -1y -8 + 5y = 46 + -1y Solving -8 + 5y = 46 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. -8 + 5y + y = 46 + -1y + y Combine like terms: 5y + y = 6y -8 + 6y = 46 + -1y + y Combine like terms: -1y + y = 0 -8 + 6y = 46 + 0 -8 + 6y = 46 Add '8' to each side of the equation. -8 + 8 + 6y = 46 + 8 Combine like terms: -8 + 8 = 0 0 + 6y = 46 + 8 6y = 46 + 8 Combine like terms: 46 + 8 = 54 6y = 54 Divide each side by '6'. y = 9 Simplifying y = 9
| -12+5x=3(x-2) | | b+3b+b+b= | | 5x+6+2x=7x-6 | | 2-a=-8 | | 5x-22+2x=20 | | -29=8+4(c+3) | | 11m-6m=22 | | kn+mp=qforp | | 3(2x-5)=9x+15 | | 40x-15=15x+39 | | 63+(2x+9)=180 | | 2(5x+1)+4=36 | | W+5w+w+w= | | 1.9+3.4=w | | 4x+11x-1=3(5x+9) | | 4x-(3x-1)=-x+12 | | ax-bx=y | | 18-30x-48=-24 | | 40x+4=3x-1 | | -3n^2+11n+28=-4n^2 | | 2x+5y=3y | | x+1*4-11=2x | | 2(x)-y=-65 | | -256a^2+36= | | 36=2(6+x) | | 4(8-3r)=-33 | | 8+2a+a=3a+2 | | 32.63=7g+3.65 | | 1.7+z=5.5 | | r^2+2r-90=-6 | | 3+m=11 | | (x+1)+5=10+(6x-2) |